Enhanced magnetic and thermoelectric properties in epitaxial polycrystalline SrRuO3 thin films. Issue 9 (16th February 2018) - Woo, Sungmin; Lee, Sang A; Mun, Hyeona; Choi, Young Gwan; Zhung, Chan June; Shin, Soohyeon; Lacotte, Morgane; David, Adrian; Prellier, Wilfrid; Park, Tuson; Kang, Won Nam; Lee, Jong Seok; et al.
Abstract : Modification of the physical properties of transition metal oxide thin films via deliberately introducing structural domain boundaries. Abstract : Transition metal oxide thin films show versatile electric, magnetic, and thermal properties which can be tailored by deliberately introducing macroscopic grain boundaries via polycrystalline solids. In this study, we focus on the modification of magnetic and thermal transport properties by fabricating single- and polycrystalline epitaxial SrRuO3 thin films using pulsed laser epitaxy. Using the epitaxial stabilization technique with an atomically flat polycrystalline SrTiO3 substrate, an epitaxial polycrystalline SrRuO3 thin film with the crystalline quality of each grain comparable to that of its single-crystalline counterpart is realized. In particular, alleviated compressive strain near the grain boundaries due to coalescence is evidenced structurally, which induced the enhancement of ferromagnetic ordering of the polycrystalline epitaxial thin film. The structural variations associated with the grain boundaries further reduce the thermal conductivity without deteriorating the electronic transport, and lead to an enhanced thermoelectric efficiency in the epitaxial polycrystalline thin films, compared with their single-crystalline counterpart.